Polyphase deformation and metamorphism of the Cuiabá group in the Poconé region (MT), Paraguay Fold and Thrust Belt: kinematic and tectonic implications - VASCONCELOS, Bruno Rodrigo (Universidade Federal do Pará, 2017)
Several deformation models have been proposed for the Paraguay Belt, which primarily differ in the number of phases of deformation, direction of vergence and tectonic style. Structural features presented in this work indicate that the tectonics was dominated by low dip thrust sheets in an initial phase, followed by two progressive deformation phases. The first phase of deformation is characterized by a slate cleavage and axial plane of isoclinal recumbent folds with a NE axial direction, with a recrystallization of the minerals in the greenschist facies associated with horizontal shear zones with a top-to-the-SE sense of movement. The second stage shows vergence towards the NW, characterized by crenulation cleavage axial plane to F2 open folds over S0 and S1, locally associated with reverse faults. The third phase of deformation is characterized by subvertical faults and fractures with a NW direction showing sinistral movement, which are commonly filled by quartz veins. The collection of tectonic structures and metamorphic paragenesis described indicate that the most intense deformation at the deeper crustal level, greenschistfacies, occurred during F1, which accommodated significant crustal shortening through isoclinal recumbent folds and shear zones with low dip angles and hangwall movement to the SE, in a thin-skinned tectonic regime. The F2 deformation phase was less intense and had a brittle to ductile behavior that accommodated a slight shortening through normal open subvertical folds, and reverse faults developed in shallower crustal level, with vergence towards the Amazonian Craton. The third phase was less pervasive, and the shortening was accommodated by relief subvertical sinistral faults.